Pengaruh Promotion, Product Quality, Price Fairness terhadap Brand Image dan Purchase Decision - Wuryan, Sophiyanto; Wahid, Jalaludin (Jurnal Informatika Ekonomi Bisnis, 2025)
The Purchase Decision is a crucial element for consumers who have previously purchased coffee or other products at the Kopilikasi coffee shop in Bekasi. This study aims to determine the influence of Promotion, Product Quality, and Price Fairness on Brand Image and Purchase Decision in the context of coffee purchases at the Kopilikasi coffee shop. Data were collected by distributing questionnaires to consumers who had previously purchased coffee at the Kopilikasi coffee shop, with an unknown number of respondents, using purposive sampling techniques, resulting in a total of 133 respondents. Data analysis was conducted using the Structural Equation Modeling – Partial Least Square (SEM-PLS) method, and the results indicate that Promotion does not have a positive effect on Brand Image, Product Quality positively affects Brand Image, Price Fairness does not have a positive effect on Brand Image, and Brand Image positively influences Purchase Decision.